A Gondwanan concept of Simplimorpha Scoble (sensu lato): a step toward clarity in the generic diagnostics of global Nepticulidae (Lepidoptera) - Stonis, Jonas R.; Diškus, Arūnas; Remeikis, Andrius; Solis, M. Alma (Zootaxa, 2018)
The genus Simplimorpha Scoble is recognized for the first time from South America. We describe a subgenus, Myrtinepticula Stonis & Diškus, subgen. nov., for three new species from the southern Andes (Chile and Argentina): Simplimorpha (Myrtinepticula) cercaria Diškus & Stonis, sp. nov., S. (M.) nielseni Remeikis & Stonis, sp. nov., S. (M.) sapphirella Remeikis & Stonis, sp. nov.; and one new species from the southwestern Amazon (Peru): S. (M.) kailai Stonis, sp. nov. We provide a pictorial differentiation scheme for Simplimorpha Scoble and Pectinivalva Scoble. We synonymize the recently erected, predominantly Australian Menurella Hoare, syn. nov. and Cosanovula Hoare, syn. nov. with Pectinivalva Scoble. We also revise the taxonomic status of the Australian Roscidotoga Hoare as a subgenus of Simplimorpha which now exhibits a Gondwanan distribution in the Southern Hemisphere, with the presence of a single species in the Mediterranean. All new taxa are illustrated with photographs of the adults and the genitalia; the leaf mines of Simplimorpha (Myrtinepticula) nielseni sp. nov. are also provided.